New-hispanic cattle-ranching in the north of the Bishopric of Michoacan, 16th-17th centuries - Navarro-López, América A. (2018)
In this work we analyze the historical and geographical processes of animal husbandry in the north of the Bishopric of Michoacán through a cartographic analysis of the period from 1550, when the New Laws were applied, to 1650, just after the implementation of the Composición de Tierras (1643). Methodologically, we undertook analysis of historical documents, such as land grants for livestock raising (large- and small-scale) and bishopric reports, to process them and elaborate their cartography in a Geographic Information System oriented to historical analysis (Historical GIS). This allows us to spatially situate the establishment of cattle ranches. Although the granting of cattle licenses rested in the purview of the civil authority, the bishopric viewed this as a disruption of the territorial interests in jurisdictions under its ecclesiastical responsibility. Research such as this, that deals with history and historical cartography, are becoming increasingly relevant, as they address important lacunae in a historiography of the study region that has largely relegated the geographical perspective to the margins.